A cardiolipina é o alvo da cardiotoxicidade dos anestésicos locais? Is cardiolipin the target of local anesthetic cardiotoxicity? - XiaoFeng Shen; FuZhou Wang; ShiQin Xu; YanNing Qian; YuSheng Liu; HongMei Yuan; QingSong Zha; ShanWu Feng; XiRong Guo; JianGuo Xu; Jie Yang (Revista Brasileira de Anestesiologia, 2010)
JUSTIFICATIVA E OBJETIVOS: Os anestésicos locais são amplamente utilizados na prevenção ou na reversão de dor aguda e no tratamento de dor crônica. A reação de cardiotoxicidade induzida pelos anestésicos locais é um evento acidental sem terapia farmacológica, exceto a infusão de intralípides relatados recentemente cujo mecanismo de ação ainda não é bem compreendido. CONTEÚDO: A cardiolipina, um fosfolipídio aniônico, desempenha papel relevante na determinação de reação respiratória mitocondrial, metabolismo de ácidos graxos e apoptose celular. A disfunção do metabolismo energético mitocondrial é sugerida em associação com a cardiotoxicidade dos anestésicos locais, a partir de um estudo in vitro de que ela talvez se deva a fortes ligações eletrostáticas entre os anestésicos locais e a cardiolipina na membrana mitocondrial. Não há, contudo, evidência experimental. Portanto, levantamos a hipótese de que as interações anestésico-cardiolipina sejam o principal determinante associado à reação de cardiotoxicidade, o que pode ser estabelecido com a adoção de métodos teóricos e biológicos estruturais. Esse modelo de interação nos daria uma pista sobre o mecanismo da cardiotoxicidade dos anestésicos locais, visando a futuras pesquisas na área de desenvolvimento de fármacos de prevenção a esse evento na prática clínica. CONCLUSÕES: A interação entre a cardiolipina mitocondrial e os anestésicos locais pode ser a principal fonte de sua cardiotoxicidade, em função de seus efeitos sobre o metabolismo energético e o estado eletrostático. BACKGROUND AND OBJECTIVES: Local anesthetics are used broadly to prevent or reverse acute pain and treat symptoms of chronic pain. Local anesthetic-induced cardiotoxic reaction has been considered the accidental event without currently effective therapeutic drugs except for recently reported intralipid infusion whose possible mechanism of action is not well known. CONTENTS: Cardiolipin, an anionic phospholipid, plays a key role in determining mitochondrial respiratory reaction, fatty acid metabolism and cellular apoptosis. Mitochondrial energy metabolism dysfunction is suggested as associated with local anesthetic cardiotoxicity, from an in vitro study report that the local anesthetic cardiotoxicity may be due to the strong electrostatic interaction of local anesthetics and cardiolipin in the mitochondria membrane, although there is a lack for experimental evidence. Herein we hypothesized that local anesthetic-cardiolipin interactions were the major determinant of local anesthetic-associated cardiotoxic reaction, established by means of theoretic and structural biological methods. This interacting model would give an insight on the underlying mechanism of local anesthetic cardiotoxicity and provide clues for further in depth research on designing preventive drugs for such inadvertent accidence in routine clinical practice. CONCLUSIONS: The interaction between local anesthetic and mitochondrial cardiolipin may be the underlying mechanism for cardiotoxicity affecting its energy metabolism and electrostatic status.